G377(P) How suitable are paediatric ambulatory attendances and what are the parental reasons for attending?. (24th May 2017) - Steele, L; Dhaliwal, J; Watson, M; Klaber, R; Coote, N
Abstract : Aims: We aimed to assess the utilisation of attendances to a paediatric ambulatory unit (PAU) in North West London and to understand parental reasons for attending the service, and where they would go if it was closed. Methods: We prospectively surveyed 95 parents attending the PAU from 18/09/15–23/10/15. A general paediatric registrar or consultant retrospectively reviewed each case to give a clinical perspective as to whether the service was utilised appropriately. Results: The most common presentations were upper respiratory tract infection, fracture/suspected fracture, head injury or facial injury, viral-induced wheeze, urinary tract infection, tonsillitis, prolonged jaundice, and hand-foot-and-mouth disease and chickenpox. Parental reasons for attending were not being able to get a general practitioner (GP) appointment (21.7%), the condition was thought to be too serious for the GP to manage or wanting specialist input (14.1%), referral by GP/midwife/nurse/health visitor (27.2%), wanting to avoid visiting the emergency department (17.4%), and other (19.5%). Following review of the cases, up to 50% of the presentations could have been appropriately managed in the community setting by the GP. For the remaining cases, 25% were deemed most suitable for management by a hospital review (including rapid referral), 20% by A+E. and 5% by midwife. In contrast, almost 50% of parents reported they would attend A+E if the PAU was not available, and less than 15% would attend the GP practice. Conclusion: Senior paediatric clinicians felt that one in two PAU attendances could have been managed in General Practice. However, there was a significant discrepancy the views of paediatricans and parents in where their child is best managed. 41% of parents attended as they were referred by a community health professional or felt the condition was too serious for the GP to manage. Important in addressing this mismatch will be improving parental confidence in their GP through improved integration of primary and secondary care services.